To solve for c, we need to isolate the variable on one side of the equation:
First, distribute the $\frac{1}{2}$ to both terms in the parentheses:
$$6c - 5 = \frac{1}{2} \cdot 6 + \frac{1}{2} \cdot 4c$$
Simplify:
$$6c - 5 = 3 + 2c$$
Subtract 2c from both sides to isolate the c term on the left side:
$$4c - 5 = 3$$
Add 5 to both sides:
$$4c = 3 + 5$$
$$4c = 8$$
Finally, divide both sides by 4 to solve for c:
$$c = \frac{8}{4}$$
$$c = 2$$
So, the solution is $c = 2$.
6c-5=\frac{1}{2}\left(6+4c\right)
1 answer